The association between OCD and Shame: A systematic review and meta‐analysis. (27th October 2022) - Laving, Michelle; Foroni, Francesco; Ferrari, Madeleine; Turner, Cynthia; Yap, Keong
Abstract: Background: Due to rumination and self‐criticism over unwanted obsessions and repetitive rituals, shame is a common emotion experienced by individuals with obsessive–compulsive disorder (OCD). Shame is also theorized to have relevance to unacceptable thoughts in OCD. However, empirical research looking at the relationship between OCD and shame is still emerging and findings have been mixed. Objectives: Our review systematically examines the association of shame with OCD and unacceptable thoughts. Methods: The last updated search was conducted across five databases between 27 and 29 February 2022. The final selection included 20 papers, 18 of which were used in the primary meta‐analysis to calculate pooled effect sizes between OCD and shame measures using a random effects model. In a separate analysis, three papers were used to calculate pooled effect sizes between shame and OCD symptom dimensions also using a random effects model. Results: The meta‐analyses identified a significant, moderate and positive correlation between total OCD and shame scores r  = .352, 95% CI [0.260, 0.438]. In addition, significant, weak and positive relationships were found between shame and three OCD symptom dimensions: unacceptable thoughts r  = .252, 95% CI [−0.467, 0.9708], harm obsessions r  = .224, CI [−0.190, 0.638] and symmetry concerns r  = .200, CI [−0.108, 0.509]. Limitations: Shame measures in the reviewed studies were not specific to OCD, and between‐study variance in the analyses examining unacceptable thoughts was significant. Conclusions: Our findings support a medium positive relationship between shame and OCD. As shame in OCD can be a barrier to seeking treatment and impair quality of life, it is imperative to address this emotion through psychoeducation, assessment and treatment.